2012
DOI: 10.2109/jcersj2.120.393
|View full text |Cite
|
Sign up to set email alerts
|

Influence of joining time and temperature on the flexural strength of joined boron carbide ceramics

Abstract: The influence of the joining time and temperature on the flexural strength of B 4 C ceramics joined using an Al sheet was investigated. The B 4 C ceramics were joined over a temperature range 6001400°C for 272 h in vacuum (10 ¹2 10 ¹4 Pa) and in an Ar atmosphere. A joining interlayer with a dense structure was found in the B 4 C joint formed at 1000°C after 2 h in vacuum, and mainly Al was present in this joining interlayer. On the other hand, some voids existed in the joining interlayer in the B 4 C joint for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 17 publications
(15 reference statements)
1
2
0
Order By: Relevance
“…b, some new phases were found to be present within the interlayer, which is demonstrated by the color contrast. The reaction between B 4 C and Al in the joining interlayer has been reported in our previous study in detail . However, the joining interlayer obtained under the conditions used in the present study was found to mainly consist of Al.…”
Section: Resultssupporting
confidence: 58%
See 1 more Smart Citation
“…b, some new phases were found to be present within the interlayer, which is demonstrated by the color contrast. The reaction between B 4 C and Al in the joining interlayer has been reported in our previous study in detail . However, the joining interlayer obtained under the conditions used in the present study was found to mainly consist of Al.…”
Section: Resultssupporting
confidence: 58%
“…In addition, the reaction between B 4 C and Al, and the contact angle of liquid Al on a B 4 C ceramics have been studied extensively, that liquid Al is easy to react with B 4 C, and some reaction mechanisms are reported between B 4 C and Al . Therefore, in our previous study, the technique of joining B 4 C ceramics was studied and B 4 C ceramics were successfully joined using Al sheets . The flexural strength of the B 4 C joint was found to be similar to that of the B 4 C base material because of the dense and crack free interlayer.…”
Section: Introductionmentioning
confidence: 98%
“…Kita et al [7,22] showed that the penetration of pure Al film with the direct coating method into cracks improves the mechanical properties of the material. In our previous study [23], the method employed by Kita et al was used to obtain coatings; however, it was limited because of some complicated parts.…”
Section: Introductionmentioning
confidence: 99%